PENGARUH PROGRAM TAHSIN AL-QURAN TERHADAP PRESTASI KERJA IMAM KOR AGAMA ANGKATAN TENTERA - Mohd Na'im Ahmad Al-Hafiz (Tesis, 2022)
The objective of this study is to analyze the influence of Tahsin Al-Quran Program (PTA) on the work performance of Imam Kor Agama Angakatan Tentera Malaysia (KAGAT) at the Institute of Training and Islamic Understanding (ILMI).